CHEMICAL ANALYSIS OF WOOD WITH BARK IN SHORT ROTATION FORESTRY SYSTEMS - Garcia, Eder Aparecido [UNESP]; Sebastiao Guerra, Saulo Philipe [UNESP]; Eufrade Junior, Humberto de Jesus [UNESP]; Sansigolo, Claudio Angeli [UNESP]; Lancas, Kleber Pereira [UNESP]; Yamaji, Fabio Minoru (Univ Federal Vicosa, 2016)
The short rotation forestry systems have high productivity in short period of time and area, however, few studies focused on the quality of forest biomass produced in these conditions. In fact, the quality of the raw material is very important for high performance of energy systems. Thus, the present work aimed to study the wood with bark from different dense forest systems, through knowledge of the gross calorific value and the main chemical components of wood - insoluble lignin, extractives and ash. Additionally, we studied the accumulation of these components in the tree over time. Clonal forestry of Eucalyptus urophylla x Eucalyptus grandis were planted in five planting spaces and three fertilization levels. At 18, 24 and 30 months after planting, sample trees was collected and disks from the DBH region were separated for the chemical analyses. Overall, the levels of insoluble lignin, extractives and ash obtained from the different treatments are in agreement with the literature and the values are similar with other older trees from the same species. The accumulation of chemical components in each tree was higher in less dense forests (more space between trees).
Keywords: Wood with bark; Eucalyptus sp; Forest energy